Gestational Trophoblastic Neoplasia: Brief Overview - Wanjari, Sanjivani (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Gestational trophoblastic neoplasia is a unique neoplastic condition that arises from fetal trophoblastic tissues and can be considered as semi-allografts. Most of the gestational trophoblastic tumours are hydatidiform moles and are mostly benign. The malignant form of gestational trophoblastic disease is called Choriocarcinoma. The disease is common in Asian and African countries, incidence in India is about 1 in 400 pregnancies. Serum \(β\)-HCG assay is the main investigation for the diagnosis and management of GTN. This is important to detect persistent trophoblastic disease and hence follow up to two years is recommended. For complete and partial moles, surgical evacuation and follow up may be sufficient. Women with non-metastatic GTN and those with metastatic low-risk GTN can be treated with single-agent chemotherapy. Methotrexate is the drug of choice when single agent chemotherapy is used. Pre-treatment HCG levels more than 40,000 U/L are indicative of high risk GTN. They are treated with multi-agent chemotherapy. The most commonly used regimen is EMA-CO. After treatment the prognosis for GTN is now excellent, nearly 100% with low-risk disease and survival is nearly 86% in high-risk disease.